A study on the implementation of total quality management (tqm) practice in Sarawak manufacturing industries - Victor, Anak Jonathan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Company's performance is the most important agenda to compete in manufacturing industries. Manufacturers nowadays are competing to plan strategy to increase their products quality and maintain their reputations in the market. The study of Total Quality Management (TQM) implementation is regarding to the method for improving products quality. TQM is the most available method or strategy that can be used by companies to inorease their products quality with an objective to increase the competitiveness in global market. The questionnaire sent through mail survey to 125 manufacturing companies in Sarawak state. From the 125 companies, only 17 of them have given a feedback. From that 17 companies, only 8 companies implementing TQM and all the analysis is based on the responses of this 8 companies. All the data that had been accepted from the respondent, was analyzed using Statistical Package for Social Science (SPSS) version 11 .5 for Window. The data analysis show that the manufacturers always fail to implementing TQM because of resistances from the employees that cannot understand the concept ofTQM in a short period of time. Beside that, the respondent also agrees that the lOp management is the most important people to encourage the implementation of TQM. This study shows that, the implementation of TQM is the most difficult process. However, there are several methods that can be used to solve the encountered problems. All the manufacturing companies in Sarawak state must implement TQM, because of their advantages. IV